Efficient Multi-Composite Cement Made of Granulated Blast Furnace Slag (GBFS) and Flash-calcined Sediment - Mahfoud Benzerzour; Duc Chinh Chu; Mouhamadou Amar; Joelle Kleib; Nor-Edine Abriak; Jaouad Nadah (Civil Engineering Journal, 2023)
The objectives of this study were to find out in detail how well granulated blast furnace slag (GBFS) could be replaced by flash-calcined sediment (SF sediment) in terms of hydration kinetics and mechanical-microstructural properties when developing an eco-friendly cement binder. The results indicated that the SF sediment substitution with a rate of 25% wt significantly improved the hydration kinetics of cement compared to the reference. This contributed to a considerable enhancement of the mechanical-microstructural properties of the mortar containing the SF sediment. By comparison with the reference, the strength of multi-composite cement-based mortar increased by 33% at 2 days and by 4.5% at 28 days, whereas its porosity decreased by 16.32% and by 12.44% for the same period. The SEM-EDS result showed that the SF sediment substitution did not significantly modify the chemical composition of the C-S-H phase, with a Ca/Si ratio range of 1.82 to 2.84 for both cement pastes. Moreover, Mg2+ and Al3+ions were two principal elements incorporated in C-S-H gels, with different ratios depending on the Ca/Si ratio of C-S-H gels. A novel model established from a combination of the curve fitting method and Power’s approach allowed for accurate prediction of the strength development of multi-composite cement-based mortars. Overall, the SF sediment substitution could be considered a promising option to develop a more eco-friendly cement binder, while the novel approach could be used as a reliable model for the strength prediction of blended cement. Doi: 10.28991/CEJ-2023-09-11-02 Full Text: PDF